Pelatihan Metode Tilawati untuk Meningkatkan Kemampuan Membaca Al-Qur’an dengan Baik dan Benar bagi Santri TPQ Al-Fath Griya Kartika Desa Cemandi - Eli Masnawati; Salwa Atika Salsabilah; Sulton Nur Falaq Marjuki (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Effective Qur'an learning is an essential aspect of Islamic religious education, particularly in improving the ability to read the Qur'an correctly and fluently. The Tilawati method is a learning approach emphasizing talaqqi musyafahah to improve letter pronunciation and tajwid. This study aims to optimize the implementation of the Tilawati method at TPQ Al-Fath Griya Kartika Desa Cemandi to enhance reading fluency and tajwid comprehension among students. The methodology employed is the Asset-Based Community Development (ABCD) approach, utilizing interviews and observations as data collection techniques and involving lecturers, students, and the community in the community service activities. The results indicate significant improvements in Qur'an reading fluency, tajwid understanding, and student motivation. Therefore, the Tilawati method is proven to be an effective learning model for Qur'an education that provides sustainable positive impacts for the surrounding community